How a Slave Has Become a Man: Frederick Douglass's Lessons in Subjection and Self-Making - Šesnić, Jelena (2013)
Slave narratives, an indigenous American genre of first-person accounts of life and experiences in slavery, are a forceful testament both to inhuman and dehumanizing, brutalizing effects of the systemic violence of the US-southern slavery and to a countering force of shaping one's self through literacy, narration, writing and testimony. Frederick Douglass's slave narrative (written in 1845) and two autobiographies (written by Douglass as a freeman respectively in 1855 and 1893) still stand out as rhetorically superb instances of, what Judith Butler in her study The Psychic Life of Power considers as a grounding paradox of the process of subjectivation: in order to bring, or will itself into being a subject is dependent either on external power or on an internalized psychic approximation of power. Whereas in her examination of “the theories of subjection, ” that ought to be seen also as instances of subjectivation, Butler reads the recesses of mind and psyche, Douglass in his first-hand account of different shades, degrees and intensities of violence entailed in day-to-day operation of the slave system demonstrates in terms of his textual practice, narrative and rhetorical devices, and careful manipulation of his narrative voice how power, mediated by violence, becomes indeed constitutive of his self-creation and emancipation. The narrator, reflecting on his gradual empowerment and the reader in the process of consuming “the scenes of subjection” become implicated in processes that, according to Butler, ambivalently conjoin the self's dependence and its incipient sense of agency, or, the subject's emergence and his continuing state of subordination.